Practical approaches to management of the marine prehistoric environment. Issue 1 (18th March 2014) - Ward, I.; Larcombe, P.; Firth, A.; Manders, M.
Abstract Since so little is still known of the marine prehistoric environment, present management actions tend to be guided by the gathering of disparate sets of data obtained as part of regulatory practice and/or from opportunistic finds that are not necessarily specifically targeted towards archaeology. Our view is that we need to develop a clearly defined set of questions about the marine prehistoric cultural resource to enable the design of targeted scientific research, as part of both the regulatory process and marine management generally. In this paper we argue that it is crucial to understand both natural and anthropogenic context, and this necessarily includes work on the Quaternary geology. Furthermore, we argue for a greater regulatory emphasis on identifying and initiating what we should do (for the long term) rather than what we can and are doing (for the short term) to identify the best means to manage the prehistoric marine environment.